Familial florid cemento-osseous dysplasia: an overview of a rare entity - Smit, Chané; Robinson, Liam; Rodrigues Gomes, Nathália; Fonseca, Felipe Paiva (Journal of Oral Diagnosis, 2024)
Familial florid cemento-osseous dysplasia (FFCOD) is distinct from the sporadic variant and may often be confused with familial conditions presenting with lesions resembling cemento-ossifying fibromas. The current review aims to elucidate the FFCOD variant better and discuss distinguishing features with sporadic florid COD. A review of the literature on FFCOD cases using Google Scholar and Pubmed was performed and summarised. A total of 11 articles with 36 patients were included in the current review. The clinical and radiologic presentations and the pertinent differences from the sporadic variant were discussed. The familial form shows advanced sclerosis and extensive distribution at a younger age, together with impacted teeth and bony expansion in the anterior mandible. Furthermore, distinguishing features from the most important differential diagnoses of other hereditary fibro-osseous conditions, including familial gigantiform cementoma (FGC), hyperparathyroidism jaw tumour syndrome (HP-JTS) and gnathodiaphyseal dysplasia (GDD) are discussed.